Uncertainty in environmental risk assessment and management: case studies of the application of the precautionary principle in Portugal - Gonçalves, V. (2018)
The application of the precautionary principle in the assessment and management of uncertain and serious potential risks to human health and the environment at the national and international levels has shown some ambiguity in the interpretation of the concept of precaution, insufficient knowledge of the potential impacts and lack of operational frameworks to support decisions. This has hindered the functioning of administrative justice and generated discretion and unpredictability in the decision process. This study intends to contribute to the debate on when and how to apply precautionary measures towards sustainability and to improve their implementation conditions. To this end it aims at clarifying how the precautionary principle has been interpreted and applied in the analysis of conflicts associated with the above-mentioned uncertain risks in a recent set of relevant court cases in Portugal in the areas of waste incineration, high voltage power lines, dam and wind farm construction. The degree of consistency of the courts’ decisions and of their reasons in the different judicial bodies was analyzed with the support of a theoretical framework based on three attributes: level of seriousness of potential hazards, level of evidence required and severity of precautionary actions taken. Different positions among courts were observed, with contradictory arguments in the same case or in similar cases. In order to counteract this situation, more explicit legal requirements and criteria for the analysis of uncertain risks and for the weighting of interests by area of activity are proposed.